indonesia Faktor – Faktor Yang Berhubungan Dengan Kualitas Hidup Pasien Gagal Ginjal Kronis Yang Menjalani Hemodialisa Di Rumah Sakit Panti Rahayu Kelor - Nugroho, Andreas Agung; Pujiastuti, Th. Tatik; Suparmi, Lucilla (STIKes Panti Rapih, 2023)
Prevalence of the Indonesian population suffering from kidney failure was 3.8 ‰, an increase compared to the prevalence of kidney failure in 2013. In Yogyakarta (DIY) it reached 20% per year, so the quality of life for kidney failure patients undergoing hemodialysis needs to be considered. The purpose of this study was to identify factors are associated with the quality of life of patients undergoing hemodialysis at Panti Rahayu Kelor Hospital. This research is a quantitative descriptive correlative study with a cross sectional survey. Population of this study were all hemodialysis patients from December 2020-February 2021 at Panti Rahayu with total of 38 respondents. Data collection method was using a questionnaire instrument and documentary study sheets. Results of the study were based on the descriptive characteristics of the respondents including the average age of 56.43 years, most of them were male, the average BMI score was 23.547, the average Hb level was 9.9 g%, the average blood pressure was 169 / 90mmHg, Symptom domain quality of life score/problem list 83,33, effect of kidney disease 78,13, burden of kidney disease 48,51, physical composite 37,57, mental composite 44,62. There is a relationship between ages with quality of life: physical composite p-value = 0.014, Hb with quality of life: physical composite p value = 0.033, diastolic blood pressure with quality of life: physical composite p value= 0.040, there is no relationship between nutritional status, type gender and blood pressure with quality of life of chronic renal failure patients undergoing hemodialysis p value> 0.05